Direct and indirect role of Fe doping in NiOOH monolayer for water oxidation catalysis. Issue 14 (31st May 2022) - Kumar, Manish; Piccinin, Simone; Srinivasan, Varadharajan
Abstract: Water oxidation activity of pristine NiOOH is greatly enhanced by doping it with Fe. However, the precise role of Fe is still being debated. Using a first‐principles DFT+U approach, we investigate the direct and indirect roles of Fe in enhancing the oxygen evolution reaction (OER) activity of NiOOH monolayers. Considering two Mars‐Van‐Krevelen mechanisms of OER based on the source of O−O bond formation, we show that a mechanism involving the coupling of lattice oxygen is generally more favorable than water nucleophilic attack on lattice oxygen. On doping with Fe, the overpotential of NiOOH is reduced by 0.33 V, in excellent agreement with experimental findings. Introducing Fe at active sites results in different potential determining steps (PDS) in the two mechanisms. The Ni sites in pristine and Fe‐doped NiOOH have the same PDS regardless of the mechanism. The Fe sites not only have the lowest overpotential but also decrease the overpotential for Ni sites. Abstract : First‐principles calculations are used to investigate the role of Fe in the water oxidation activity of Fe‐doped NiOOH monolayers. Fe is found to not only lower the overpotential at Ni active sites but also directly affect the oxygen evolution through a thermodynamically favourable lattice oxygen mechanism with significantly lowered overpotential.